2020
DOI: 10.1088/1742-6596/1342/1/012073
|View full text |Cite
|
Sign up to set email alerts
|

Modulations in Spectra of Galactic Gamma-ray sources as a result of photon-ALPs mixing.

Abstract: Axion like particles (ALPs) are fundamental pseudo scalar particles with properties similar to Axions which are a well-known extensions of the standard model to solve the strong CP problem in Quantum Chromodynamics. ALPs can oscillate into photons and vice versa in the presence of an external tranversal magnetic field. This oscillation of photon and ALPs could have important implications for astronomical observations, i.e. a characteristic energy dependent attenuation in Gamma ray spectra for astrophysical sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The γ-ray data have been widely used to search for ALP signals [16][17][18][19][20][21][22][23][24][25]. The Fermi Collaboration searched for ALPs from the radio galaxy NGC 1275, located in the Persus cluster, which has relatively good magnetic field measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The γ-ray data have been widely used to search for ALP signals [16][17][18][19][20][21][22][23][24][25]. The Fermi Collaboration searched for ALPs from the radio galaxy NGC 1275, located in the Persus cluster, which has relatively good magnetic field measurements.…”
Section: Introductionmentioning
confidence: 99%
“…By studying modulation behaviors in spectra of 6 γ-ray pulsars, Majumdar etal. [23,24] reported intriguing indications of photon-ALP mixing. Even stronger evidence was obtained in a further analysis of 12 non-Galactic plane pulsars [25].…”
Section: Introductionmentioning
confidence: 99%
“…The large-scale Galactic magnetic field model developed by Jansson & Farrar [51] (Bfield1) is adopted in our work, which has been wildly used in the relevant investigations [29][30][31][32][33]. This model composes of a disk field, an extended halo field and out of plane component and provides a best fit to WMAP7 Galactic synchrotron emission map and more than 40,000 extragalactic rotation measures (RM) data.…”
Section: Photon-alp Oscillation In the Milky Way Magnetic Fieldmentioning
confidence: 99%
“…Collaboration [23] and Zhang et al [28] without significant signal of ALPs found. The γ-ray spectra of bright pulsars [29][30][31] and SNRs [32] obtained from the Fermi-LAT data show intriguing indications for the photon-ALP oscillation, but the best-fit parameters are in tension with the limit from the CAST helioscope. Besides, Liang et al found that higher ALP mass region of the ALP parameter space can be probed by the H.E.S.S.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation